A Markovian Analysis of Statutory Disputes Settlement Mechanisms during the Third Civilian Regime in Nigeria (1999-2013) - Ikeije, Ugochukwu U.; Anyim, Francis C. (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
This study focused on the statutory trade disputes settlement mechanisms during the third republic in Nigeria. Its main objective is to analyze the probabilities of trade disputes transiting from one mechanism to another and find out which statutory mechanism has higher level of usage than others in the third civilian regime in Nigeria . S urvey research design that relied on the secondary data from the existing records of the relevant ministries and agencies such as Federal Ministry of Labour and Employment, Central Bank of Nigeria Annual Statistical Bulletin and National Bureau of Statistics (various years) was used. Descriptive statistics involving frequencies and percentages were used in analyzing the data from the records of these various ministries and agencies. These data were presented in tabular forms for easy interpretation. Markov chain which is a special case of stochastic process was used in analyzing the probabilities of transition from one mechanism to another and served as the basis for testing the hypothesis. It was found that conciliation as a dispute settlement mechanism has higher level of usage (highest probability value of 0.3552) than other statutory mechanisms within the period covered by this study. Based on this finding, it was recommended that parties in trade disputes within the Nigerian industrial relations environment should explore the option of submitting trade disputes that could not be settled internally to conciliation. Keywords: Statutory, Conciliation, Arbitration, Adjudication, Trade Disputes, Markov Chain